The Heavy Metal Contamination in Shallow Groundwaterof Semarang Coastal Areas - Baskoro Rochaddi; Chrisna Adhi Suryono (Universitas Diponegoro, 2013)
Heavy metals in the aquatic environment have to date come mainly from naturally occurring geochemical materials. However, this has been enhanced by human activities such as boat activity, industrial effluents, domestic sewage etc. An attempt was made to determine the level of trace metals such as Mercury (Hg), Lead (Pb), Iron (Fe), Chromium (Cr) and Copper (Cu). The physico-chemical and trace metal contents of water samples from coastal zone of Semarang were assessed using Atomic Absorption Spectrophotometer technique. Results indicated that low variation existed among some physico-chemical parameter (pH, temperature, salinity). In the water sample colour, taste and odor were investigated. Heavy metal levels (mg L-1) in the water were Cr 5.083 + 1.59, Pb 5.52 + 1.34, Fe 1.199 + 1.29. However, Hg and Cu were not detected in any of the samples. Comparison of the metal contents in the water sample with World Health Organization (WHO) limits and Indonesian Drinking & Domestic Water Quality Standard for Ground Water showed that the mean levels of Fe, Pb, Cr were exceeded the maximum permissible levels for drinking water. This work has conclusively proven the presence of dangerous heavy metal contamination of the groundwater supply in the coastal area of Semarang. Key words: Physico-chemical parameters, heavy metals, Atomic Absorption Spectrophotometer